2013
DOI: 10.1002/jssc.201300678
|View full text |Cite
|
Sign up to set email alerts
|

SPE of 5-lipoxygenase metabolites and the effect of head-column field-amplified sample stacking in MEKC

Abstract: The SPE of leukotrienes and eicosatetraenoic acids using anion exchange materials was compared to the classical extraction with C18 columns. A silica-based strong anion exchanger, a polymer-based weak anion exchanger, and a polymer-based mixed-mode strong anion exchanger were studied. All anion exchange materials displayed a higher recovery of the analytes with values between 70 and 90% when extracting standard solutions and analyzing by HPLC. The effect was less pronounced for the analysis of the compounds in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Therefore, the authors compared the results of the C18 SPE of LTs and HETEs with those obtained from HPLC separations using a SAX (Hypersep Verify‐AX), a polymer‐based weak anionic exchanger (Strata X‐AW) and a polymer‐based mixed‐mode SAX (Bond Elut Plexa PAX). The authors demonstrated that higher recovery of the analytes could be obtained using anion‐exchange columns . The same research team wished to optimize the MEKC method to make it more suitable for use with more polar arachidonic acid metabolites and therefore set out to develop a MEEKC method.…”
Section: Free Fatty Acidsmentioning
confidence: 99%
“…Therefore, the authors compared the results of the C18 SPE of LTs and HETEs with those obtained from HPLC separations using a SAX (Hypersep Verify‐AX), a polymer‐based weak anionic exchanger (Strata X‐AW) and a polymer‐based mixed‐mode SAX (Bond Elut Plexa PAX). The authors demonstrated that higher recovery of the analytes could be obtained using anion‐exchange columns . The same research team wished to optimize the MEKC method to make it more suitable for use with more polar arachidonic acid metabolites and therefore set out to develop a MEEKC method.…”
Section: Free Fatty Acidsmentioning
confidence: 99%
“…Indeed, the results of our preliminary experiments using an anion-exchange SPE process revealed that the extraction efficiencies of prostaglandins and thromboxanes were <40 % (data not shown). To overcome these issues, we examined the lipid extraction conditions using mixed-mode SPE, which has been used in lipid biology to analyze fatty acid metabolites [27,28]. Although this approach is very attractive, its application has been limited because it can only be applied to a small number of lipids.…”
Section: Construction Of Mixed-mode Spementioning
confidence: 99%
“…With this in mind, reversed-phase/anion-exchange SPE (mixedmode SPE) was evaluated in the current study for the extraction of polar lipids from biological samples. Although mixed-mode SPE has been reported as a novel extraction approach for fatty acid metabolites [27,28], this technique has only been applied to a limited number of lipids and a detailed method has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Various online sample preconcentration techniques without modification of the instrument provide convenient approaches for sensitivity improvement in CE. Field-amplified sample stacking (FASS) is simple yet effective, only requiring samples with low conductivity. Sample may be injected electrokinetically (field-amplified sample injection (FASI)) or hydrodynamically (FASS and large-volume sample stacking (LVSS)). , FASI (also called head-column FASS (HC FASS)) is not limited by sample injection volume and thus often provides greater sensitivity enhancements than FASS and LVSS. It has generated over 1000-fold sensitivity enhancements for drug analysis of clinical samples. It has been implemented in other applications utilizing CZE, MEKC, , CE-LIF, CE-mass spectrometry, CE-flow injection, , DNA, oligosaccharides analysis, and microfluidic electrophoresis. …”
mentioning
confidence: 99%
“…It has generated over 1000-fold sensitivity enhancements for drug analysis of clinical samples. 33−37 It has been implemented in other applications utilizing CZE, 38−41 MEKC, 42,43 CE-LIF, 44 CE-mass spectrometry, 45−48 CE-flow injection, 49,50 DNA, 51 oligosaccharides analysis, 52 and microfluidic electrophoresis. 53 Various sample stacking approaches have been explored in various separation modes of CE for protein analysis.…”
mentioning
confidence: 99%